THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON PROFITABILITY IN AGRICULTURE SUB-SECTOR COMPANIES REGISTERED IN 2018-2022 ON THE INDONESIAN STOCK EXCHANGE - Grefi, Grefi Simanjuntak; Magit Les Denny Tewu; Ktut Silvanita Mangani (Universitas Kristen Indonesia, 2024)
Corporate governance is a set of guidelines used by companies in managing their operations with the hope of maintaining productivity and sustainability, so as to optimize company profits. The objective of this research is to evaluate the impact or influence of corporate governance, both partially and simultaneously, on profitability in agricultural sub sector enterprises publicly listed on the Indonesia Stock Exchange. Assessment of corporate governance is carried out through indicators such as the composition of the board of commissioners, board of directors, audit committee and institutional ownership, while profitability uses return on assets (ROA). This research utilizes a quantitative methodology utilizing secondary data acquired from financial reports, company annual reports, and corporate governance implementation reports. The data analysis methods used include quantitative descriptive statistics, data normality tests, multiple linear regression analysis, additionally conducting hypothesis testing utilizing the t test and F test. The outcomes of the t test research indicates that the variables concerning of the board of commissioners, board of directors and audit committee do not have a significant effect on profitability (ROA) agricultural sub-sector enterprises publicly listed on the Indonesia Stock Exchange. However, institutional ownership has a significant effect on the company's profitability (ROA). The results of the study indicate the f test indicates that the variables board of commissioners, board of directors, audit committee and institutional ownership have a significant influence on the profitability (ROA) of agricultural sub sector enterprises publicly listed on the Indonesia Stock Exchange. Keywords: Corporate Governance, ROA